Safety and health conditions in construction sites from the perspective of site safety coordination - Rocha, Ricardo (2020)
The numerous risk factors present in the construction sector make it one of the factors with the highest number of accidents at work, and it can drive to the development of occupational diseases. So, it becomes important to comply with national and community legal provisions, namely, compliance with Decree-Law nº. 273/2003, of 29 October. The latter foresees the mandatory presence of a Health and Safety Coordinator in shipyards, with no exceptions discriminated in the legal diploma. The main objective of this study was to verify the safety and health conditions in civil construction works, analysing the compliance with the Safety and Health Plan of the construction phase and the legal requirements in force. In order to achieve the objective of this study, a verification tool was developed, divided into nineteen chapters and applied to thirty construction sites, where the number of questions in Compliance (C) and Non-Compliance (NC) was verified. After its application, it was highlighted that the chapter with the highest absolute number of NC corresponded to works at height. The presence of a Safety Coordinator on site is essential in order to guarantee the application of safety measures, namely those described in the Safety and Health Plan of the site, compliance with current legislation, and the guarantee of safety and health conditions for all workers on site